2010
DOI: 10.1021/nn901593c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fabrication Parameters on Three-Dimensional Nanostructures and Device Efficiency of Polymer Light-Emitting Diodes

Abstract: By using 10 kV C(60)(+) and 200 V Ar(+) ion co-sputtering, a crater was created on the light-emitting layer of phosphorescent polymer light-emitting diodes, which consisted of a poly(9-vinyl carbazole) (PVK) host doped with a 24 wt % iridium(III)bis[(4,6-difluorophenyl)pyridinato-N,C(2)] (FIrpic) guest. A force modulation microscope (FMM) was used to analyze the nanostructure at the flat slope near the edge of the crater. The three-dimensional distribution of PVK and FIrpic was determined based on the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Co‐sputtering with a 10 kV C 60 + and a 0.2 kV Ar + beam is known to preserve the chemical structure of the remaining surface for various organic/polymeric materials . Using the co‐sputtering beam as the ionization source, molecular D‐SIMS spectra were also acquired (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Co‐sputtering with a 10 kV C 60 + and a 0.2 kV Ar + beam is known to preserve the chemical structure of the remaining surface for various organic/polymeric materials . Using the co‐sputtering beam as the ionization source, molecular D‐SIMS spectra were also acquired (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The apparatus is based on a PHI 5000 VersaProbe (ULVAC‐PHI, Chigasaki, Japan) scanning X‐ray microprobe system operated at a base pressure of <1 × 10 –7 Pa, which was achieved by evacuation using ion getter pumps. The Ar + ion source was operated at 0.2 kV and 300 nA (measured on an Au target) using a floating voltage of 500 V. A voltage setting of 0.2 kV has been previously found to preserve the chemical structure of the remaining surface for various organic/polymeric materials while yielding a more stable sputtering rate . The ray path contained a 1° bend to filter fast Ar atoms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The same SIMS experiments show these atoms to have back‐migrated toward their original electrodes upon a reverse bias at 14 V for 120 min. Our prior study showed that there existed Al spikes protruding into the organic layer . Those Al‐spike facing layer materials would experience a tremendously high electric field and break down electrically at elevated voltages due to their limited dielectric strength.…”
Section: Resultsmentioning
confidence: 99%